Effects of Tp53 Gene Mutations on the Survival of Non-Small Cell Lung Cancer (NSCLC); A Short Review - Zhang C; Yang C; Shi Q (Cancer Management and Research)
Chi Zhang,1,2,* Chao Yang,3,* Qingming Shi1,2 1Department of Oncology, Anhui Chest Hospital, Hefei, 230022, People’s Republic of China; 2Anhui Medical University Clinical College of Chest, Hefei, 230022, People’s Republic of China; 3Department of Urology, Anhui Provincial Children’s Hospital, Hefei, 230022, People’s Republic of China*These authors contributed equally to this workCorrespondence: Qingming Shi, Email shqm0324@163.com, shqm0324@hotmail.comAbstract: Non-small cell lung cancer (NSCLC) is the leading cause of cancer-related deaths worldwide. Mutations within the TP53 gene represent critical molecular events in NSCLC, contributing to the tumorigenesis in the pulmonary epithelial tissues. TP53 is a widely researched prognostic indicator in NSCLC, and pathological investigations have revealed a weak to mild negative predictive effect for TP53. Mutated p53 protein may have some pro-oncogenic impact, and the variations may change tumor inhibitors into oncogenes. The diverse mutational spectrum of TP53 in NSCLC with different mutations is linked to varied treatment responses. In contrast, first-line chemotherapeutics to this progress are limited, however, randomized trials with new chemotherapeutics have shown significant survival benefits. This review highlighted the critical influence of TP53 gene mutations on pathological-sensitivity and overall survival outcomes in NSCLC. Further research is needed to explore TP53 mutation-specific pathways and their effects on NSCLC progression and treatment effectiveness. Keywords: non-small cell lung cancer, TP53 gene, treatment, survival analysis, mutations